Risk factors in an HIV-infected population for refraining from specialist care. Issue 10 (2nd October 2016) - van Andel, E.; Been, S.K.; Rokx, C.; van der Ende, M.E.
ABSTRACT: Background : To obtain maximal benefit of combination antiretroviral therapy (cART), HIV-infected patients should be retained in medical care. Missed clinical visits are independently associated with all-cause mortality among HIV-infected patients. Our objective was to identify risk factors and patient-reported reasons for nonattendance at outpatient clinic appointments. Design and methods : We conducted a cross-sectional case-control study among 447 HIV-infected patients attending the outpatient clinic between March and July 2014. Patients with missed appointments from January 2013 onwards were included as cases and compared to a random selection of same-day controls without missed appointments during the same period. Clinical and socio-demographic characteristics were collected from clinical records and an interviewer-administered questionnaire. Additionally, reasons for nonattendance and possible solutions for future better attendance were addressed in the questionnaire. Multivariable logistic regression analysis was used to determine independent risk factors for nonattendance. Results : A total of 224 cases and 223 controls were included. Independent risk factors for nonattendance were: (i) age <30 years (odds ratio (OR) 7.2; 95% CI: 3.2–16.3 versus ≥50 years); (ii) African region of origin (OR 2.8; 95% CI: 1.5–5.0 versus Western origin); (iii) having children <12 years of age (OR 2.1; 95% CI: 1.1–4.1); (iv) history of drugs- or alcohol abuse (OR 4.4; 95% CI: 1.8–10.8); (v) no cART (OR 2.5; 95% CI: 1.1–5.3) or HIV-RNA >400 copies/ml while receiving cART (OR 3.5; 95% CI: 1.3–9.6). The main reason given for nonattendance was failure to remember the appointments (44%). Most patients would prefer to receive an appointment reminder by SMS (80% of the cases and 55% of the controls). Conclusion : Missing outpatient clinic appointments were associated with available clinical characteristics. Nonattendance may be prevented by sending routine SMS reminders prior to the next appointment.